This is no Child's Play: Yrjo Hirn, savage slots and other anthropological hernias. Issue 2 (3rd April 2021) - Alleyne, Osei
ABSTRACT: Whereas (Hirn, Yrjö 1916 . Barnlek. Helsingfors: Söderström & Co) Barnlek has only recently resurfaced, translated as it has been into English, contemporary scholars committed to social justice must engage both its latent and overt colonialist thinking. While Hirn's work resonates as an early intervention against a then-institutional dismissal of childrens' games as beneath anthropological study, the Finnish scholar's rehearsal of more broadly imperialist language in his chapter "On Children's Games, " begs a historic critique that places it in the context of ongoing Euro-American social upheavals.